PEMBERDAYAAN DUKUNGAN KELUARGA TERHADAP PENINGKATAN KEPATUHAN PENERAPAN PROTOKOL KESEHATAN PENCEGAHAN COVID-19 - Beni Satria; Felix Kasim; Anggi Isnani Paranduri; Irmayani Irmayani; Sri Melda Br Bangun; Kuat Sitepu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
COVID-19 became a world health problem in early 2020. This case began with information from the WHO on December 31, 2019 which stated that there was a cluster case of pneumonia with unclear etiology in Wuhan City, Hubei Province, China. This case continued to grow until there were reports of deaths and imports outside China. In Indonesia, on March 2, 2020, Indonesia has reported 2 (two) confirmed cases of COVID-19. Cases are increasing and spreading rapidly throughout Indonesia. This paper aims to empower family support to improve compliance with the implementation of COVID-19 prevention health protocols. The method of implementing the activity is in the form of observation and providing health education about the application of health protocols in an effort to prevent COVID-19 to the community, based on the results of activities carried out by the community enthusiastically welcoming this activity. Through this activity, it is hoped that there will be an increase in compliance in the application of the COVID-19 prevention health protocol so as to suppress the decline in COVID-19 cases.